Amino Acid Assisted Incorporation of Dye Molecules within Calcite Crystals. Issue 28 (10th June 2018) - Marzec, Bartosz; Green, David C.; Holden, Mark A.; Coté, Alexander S.; Ihli, Johannes; Khalid, Saba; Kulak, Alexander; Walker, Daniel; Tang, Chiu; Duffy, Dorothy M.; Kim, Yi‐Yeoun; Meldrum, Fiona C.
Abstract: Biomineralisation processes invariably occur in the presence of multiple organic additives, which act in combination to give exceptional control over structures and properties. However, few synthetic studies have investigated the cooperative effects of soluble additives. This work addresses this challenge and focuses on the combined effects of amino acids and coloured dye molecules. The experiments demonstrate that strongly coloured calcite crystals only form in the presence of Brilliant Blue R (BBR) and four of the seventeen soluble amino acids, as compared with almost colourless crystals using the dye alone. The active amino acids are identified as those which themselves effectively occlude in calcite, suggesting a mechanism where they can act as chaperones for individual molecules or even aggregates of dyes molecules. These results provide new insight into crystal–additive interactions and suggest a novel strategy for generating materials with target properties. Abstract : Combined benefits : Remarkable control over crystallisation processes can be achieved by employing combinations of soluble additives. Focussing on the combination of amino acids with common dye molecules, it is shown that certain amino acids can drive efficient dye occlusion, yielding strongly coloured single crystals. Colourless crystals form in the absence of the amino acids. The ability of amino acids to chaperone partner molecules into the crystal lattice is governed by their own occlusion activity.